Tramadol is a performance-enhancing drug in highly trained cyclists: a randomized controlled trial - Mauger, A. R.; Thomas, T.; Smith, S. A.; Fennell, C. R. J. (Journal of Applied Physiology, 2023)
Tramadol is a potent narcotic analgesic reportedly used in multiple sports to reduce exertional pain and confer a performance advantage. This study sought to identify whether tramadol enhances performance in time trial cycling. Twenty-seven highly trained cyclists were screened for tramadol sensitivity and then attended the laboratory across three visits. Visit 1 identified maximal oxygen uptake, peak power output, and gas exchange threshold through a ramp incremental test. Participants returned to the laboratory on two further occasions to undertake cycling performance tests following the ingestion of either 100 mg of soluble tramadol or a taste-matched placebo control in a double-blind, randomized, and crossover design. In the performance tests, participants completed a 30 min non-exhaustive fixed intensity cycling task at a heavy exercise intensity (272 ± 42 W), immediately followed by a competitive self-paced 25-mile time trial (TT). Following removal of two outlier data sets, analysis was completed on n = 25. Participants completed the TT significantly faster (d = 0.54, P = 0.012) in the tramadol condition (3758 s ± 232 s) compared with the placebo condition (3808 s ± 248 s) and maintained a significantly higher mean power output (+9 W) throughout the TT (np2 = 0.262, P = 0.009). Tramadol reduced perception of effort during the fixed intensity trial (P = 0.026). The 1.3% faster time in the tramadol condition would be sufficient to change the outcomes of a race and is highly meaningful and pervasive in this cohort of highly trained cyclists. The data from this study suggests that tramadol is a performance-enhancing drug.